e=mc2: A Biography of the World's Most Famous Equation - David Bodanis (Pan Books, 2001)
'By the end of the astonishing "E=mc2", a dedicated reader will have achieved, if only by osmosis, an understanding of Einstein's theory of relativity and feel quite at ease dining with Nobel Prize winners. It's a lucid, even thrilling study: the very best kind of science journalism. I didn't know I could know so much.' - Fay Weldon, Books of the Year, "Washington Post". In 1905, Albert Einstein produced five historic papers that shattered many cherished scientific beliefs. One of those papers introduced the theory of special relativity and his legendary equation, E=mc2. Generations have grown up knowing that equation changed the shape of our world, but without understanding what it really means and why it is so significant. In this fascinating biography, David Bodanis tells the story of one of the greatest scientific discoveries in history. He looks at the elements 'e', 'm' and 'c'; and honours the scientists whose landmark discoveries paved the way for Einstein. He plots the course of the equation through the twentieth century, showing how our lives have been revolutionized by its applications; and looks far ahead to the future. But as with any biography, it is the human stories that really ignite the subject - stories of love, courage and tragedy, of near misses, disappointments and disasters that, brought together by Bodanis in this remarkable book, turn Einstein's seemingly impenetrable theory into a dramatic and accessible human achievement. 'Both informative and highly readable..."E=mc2" is a wonderful romp through Einstein's famous formula. This is everything a popular science book should be' - "Daily Express". 'Bodanis himself seems like an intellectual thermonuclear explosion, a kind of Jonathan Miller on speed...This is an outstanding introduction to relativity by a gifted practitioner of popular science' - "Independent". 'With skill and plenty of colourful anecdotes, Bodanis traces the intellectual ancestry of E=mc2...fast moving and entertaining' - "The Times." '"E=mc2" reveals, amongst other wonders, how many women physicists were involved in the story, which makes this morally improving, as well as fascinating reading' - George Walden, Books of the Year, "Sunday Telegraph".